(3JhGQjN Sfi edhc GdCQVs ((3GHh HcQ Hf YHO Gddg Gdabgi s)
(3ChdgG (B:s
(3aGdaQS cdgG HCSQgG JRYe Cf GHJOGA GdJfGhjd cGf ef GdQLd jbGd dg cjheQK cd TGg s
(3BNQgG (B:s
(3hHbhG Ydi GNJdGa ef MGdge acGfJ eOI GdSff GdJi eVJ dge ajgG gPg GdMGd hgj GdSfhf GdefShHI Edi GdeOjQjI hGdbVGg ef Hfi ESQGFjd Je HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs